SOCIAL AND FINANCIAL PERFORMANCE OF RURAL MICROFINANCE INSTUTION UED-SP BAKTI MULYA TALANG MULYA VILLAGE BATANG CENAKU SUBDISTRICT INDRAGIRIHULU REGENCY - riyanto, Adi; Rifai, Ahmad; Tarumun, Suardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to analyze social and financial performance of microfinance institutions UED-SP Bakti Mulya. Social performance analyzed using Microfinance Information exchange (MIX) soscial performance standard report, and financial performance analyzed using 17 PEARLS ratio. Analysis of the UED-SP social peformance has reached the social mission and goals the cumulative volume of loans 19.42 percent, and the higher growth of loans volume is the agricultural sector 39.18 percent. The poor borrowers 23.33 percent and volume of loans increased 35.06 percent. Internal systems increased on a variety of loan products and increased incentives for staff. The output and outcome UED-SP was increasing in average annual, outreach of the women borrowers, the borrower of productive economic in the agricultural sector, poor borrowers, and the volume of saving. Monetary performance LKM UED-SP Talang Mulya show from 17 indicator ratio of PEARLS there are 8 indicator residing in condition is not ideal cover protection ratio ( protection) ( P1), and ( P2), lending ratio circulate ( E1), Share deposit ratio ( E7) and operating expenses ratio (R9),Rasio not yield ( L3), growth of share deposit ( S5), and growth of institute capital (S6) show condition is not ideal. Implication Policy of Social Performance that is organizerÂ  require to follow training related to gender sensitivitas, Need the existence of development of product innovation, accepted incentive staff have to pursuant to performance. Implication policy of monetary performance have to cast aside risk reserve fund to avoid arrears risk. Keywords: Financial Peformance, UED-SP, Social Peformance Â